Effects of Bacillus coagulans GBI-30, 6086 probiotic added to extruded pet food on apparent nutrient digestibility, stool quality, intestinal health indicators, and fecal microbiota of healthy adult dogs - Acuff, Heather Lynn (Kansas State University, 2021)
Bacillus coagulans GBI-30, 6086 is a spore-forming bacterium reported to survive environmental stresses, heat processing, and extreme-pH conditions, which are characteristics that support its utility in commercial food applications. Extrusion is the most widely used method to produce commercial dog foods, however no previous studies have examined the survivability of this strain through extrusion or its efficacy with regards to gastrointestinal health of dogs. Thus, the objectives were to determine the viability of Bacillus coagulans GBI-30, 6086 through extrusion cooking and drying, and its effects on nutrient utilization, intestinal health, and the fecal microbiota of healthy adult dogs. Two experiments were conducted to determine the reduction in viability of the organism at graded flour inoculation doses (0, 6.2, 6.7, and 7.3 log₁₀ CFU/g) through extrusion with varying levels of extruder water inputs (10, 12, and 20 kg/h), extruder screw speeds (400, 500, and 600 rpm), and dryer settings (49 °C for 10 min; 107 °C for 16 min; and 66 °C for 46 min). The low SME extrusion conditions (in-barrel moisture of 35%, extruder screw speed of 400 rpm, and specific mechanical energy of 129 kJ/kg) resulted in the greatest retention (P<0.05), with a mean log₁₀ reduction of viable spores of 0.44, 2.15, and 2.67 for the low, moderate, and severe extrusion conditions, respectively. Viability of spores subjected to three dryer conditions were observed to be similar across all treatments. To evaluate the effects of Bacillus coagulans on nutrient utilization, stool quality, and intestinal health indicators in dogs, extruded diets containing graded levels of probiotic applied either to the base ration before extrusion or to the exterior of the kibble as a topical coating after extrusion were randomly assigned to ten individually housed adult Beagle dogs (7 castrated males, 3 spayed females) of similar age (5.75 ± 0.23 years) and body weight (12.3 ± 1.5 kg). Apparent total tract digestibility of organic matter, crude protein, crude fat, and gross energy calculated by the marker method were numerically greatest for dogs fed 9 log₁₀ CFU/d with increases (P < 0.05) observed in gross energy and organic matter digestibility compared to the negative control. No significant changes were observed in food intake or fecal scores, moisture content, pH, ammonia, short-chain fatty acids, or branched-chain fatty acids for the probiotic-containing treatments compared to a non-probiotic control. To evaluate the effects of Bacillus coagulans on the fecal microbiota of dogs, fresh fecal samples were analyzed by 16S rRNA gene pyrosequencing. Firmicutes comprised the greatest proportion of observational taxonomic units (mean 81.2% ± 5), followed by Actinobacteria (mean 9.9% ± 4.4), Bacteroidetes (mean 4.5% ± 1.7), Proteobacteria (mean 1.3% ± 0.7), and Fusobacteria (mean 1.1% ± 0.6). No evidence of a shift in predominant phyla, class, family, or genus taxonomic levels were found apart from the Bacillus genus, which was observed to have a greater relative abundance (P=0.0189) in the low probiotic coating (5.92 x 10⁵ CFU/g) and high probiotic coating (6.84 x 10⁶ CFU/g) treatment groups compared to the extruded probiotic (1.06 x 10⁴ CFU/g) and non-probiotic control treatments. Alpha-diversity indices (Richness, Chao1, ACE, Shannon, Simpson, Inverse Simpson, and Fisher) were similar for all treatments. Beta-diversity metrics (principal coordinate analysis) did not provide evidence of clustering for UniFrac distances among treatment groups. Overall, Bacillus coagulans GBI-30, 6086 retained varying degrees of viability during extrusion and drying of pet food. As a functional probiotic, our data supports an improvement in nutrient utilization and maintenance of stool quality, intestinal health indicators, and fecal microbiota in healthy adult dogs at a dose of 9 log₁₀ CFU/day.
Keywords: Bacillus coagulans; Probiotics; Extrusion; Dogs; Nutrient utilization; Intestinal health; Fecal microbiome